Perlindungan Hukum Terhadap Hak Pekerja Atas Perolehan Jaminan Sosial Tenaga Kerja - Muhammad Zainuddin (Jatiswara, 2016)
Social security is a right of everyone, without exception, including workers / laborers as the provisions of Article 28H paragraph (3) of the Constitution of 1945, which reads; "Everyone is entitled to social security that allows development of his or her self as dignified human beings," as well as the mandate of the Declaration of the United Nations (UN), 1948 on Human Rights, and has also affirmed in the Convention on the International Labour Organization (ILO) No. 102 of 1952, which recommends that all States to provide minimum protection to all workers. In the decree of the People's Consultative Assembly of Indonesia Number X / MPR / 2001, to determine the tasks the President to form the National Social Security System in order to provide a comprehensive social protection and integration. On February 17, 1992, the government put forth Law No. 3 of 1992 on Social Security Workers (State Gazette of the Republic of Indonesia Year 1992 Number 14, Additional State Gazette No. 3468), to provide protection to every worker / laborer as the right of every person without exception. However, the right of workers / laborers to obtain workers' social security that provides protection against occupational accidents, illness, pregnancy, maternity, old age and death, is only obtained if the employer where workers / laborers to the Organizing Body, namely PT. Social Security, as stipulated in the provisions of Article 4 paragraph (1), which determines that; "Program of social security referred to in Article 3 shall be realized by companies for workers who perform work in labor relations in accordance with the provisions of this law."